OCA optical adhesive for folding screens and its preparation method and application
By adding modified allyl polyether derivatives and modified silica to OCA optical adhesive, the problems of blue light protection, heat stability and aging resistance in folding screens are solved, higher viscosity and tensile strength are achieved, and the performance of the folding screen is improved.
Patent Information
- Application Number
- CN202211485232.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2042-11-24
AI Technical Summary
Existing OCA optical adhesives lack blue light protection, heat stability and aging resistance in folding screens, making it difficult to meet the usage requirements of folding screens.
By adding modified allyl polyether derivatives and modified silica into OCA optical adhesive, its blue light protection, heat stability and aging resistance are improved. The modified allyl polyether derivatives participate in the copolymerization process, and the modified silica surface is modified with antioxidants to enhance the interface performance.
The anti-blue light performance of OCA optical adhesive has been improved, and its heat stability and aging resistance have been enhanced, ensuring good adhesion and tensile strength in folding screens and inhibiting thermal degradation.
Smart Images

Figure CN115895523B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical adhesive technology, and in particular to an OCA optical adhesive for a folding screen, and a preparation method and application thereof. Background Art
[0002] In recent years, in order to make large-screen electronic devices such as mobile phones more portable, foldable electronic devices have gradually entered the market and are deeply loved by consumers. Foldable electronic devices require matching foldable displays, and displays require adhesives to fix the various components in their structure. OCA optical adhesive has the characteristics of high light transmittance, water resistance, and solvent resistance, and has gradually become one of the adhesives for bonding display components of electronic devices such as mobile phones and tablets. In folding screens, OCA optical adhesive needs to have high tensile properties to avoid breakage during continuous bending, resulting in irreversible damage at the bends. In addition, mobile phones and other electronic devices will inevitably generate heat during use, which requires OCA optical adhesive to have strong heat resistance and aging resistance to prevent OCA optical adhesive from aging, yellowing, or even losing adhesion. In addition, studies have shown that short-wave blue light emitted by electronic products can directly reach the retina and cause great damage to the human eye. As people's dependence on electronic products such as mobile phones continues to increase, anti-blue light has gradually become an essential requirement for electronic products. Therefore, the OCA optical adhesive used in folding screens needs to have stronger tensile resistance, heat stability, aging resistance, and anti-blue light properties.
[0003] The Chinese patent application with publication number CN114907781A discloses a high-performance OCA optical adhesive for folding screens and a preparation method thereof. By adding nano-sized modified silica hydrosol to the OCA optical adhesive system and using an antioxidant, the OCA optical adhesive can have excellent yellowing resistance and aging resistance, which is conducive to the widespread application of OCA optical adhesive in folding screen products. However, anti-blue light is one of the key issues of folding screen products. This patent does not make anti-blue light improvements to the OCA optical adhesive, and in fact there are certain limitations on the application of OCA optical adhesive in the folding screen field. Summary of the Invention
[0004] The purpose of the present invention is to provide an OCA optical adhesive for stacked screens, a preparation method and application thereof. By using modified nano-silica as a filler, the tensile resistance, heat stability and aging resistance of the OCA optical adhesive are improved. By using modified allyl polyether derivatives to participate in the copolymerization process, the OCA optical adhesive is given excellent anti-blue light performance, and the heat stability of the OCA optical adhesive is further enhanced.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An OCA optical adhesive for folding screens comprises the following raw materials in parts by weight: 50-60 parts of isobutyl acrylate, 20-40 parts of butyl methacrylate, 2-5 parts of hydroxyethyl acrylate, 1-3 parts of glycidyl acrylate, 0.5-1 part of a modified allyl polyether derivative, 1-2 parts of modified silicon dioxide, and 0.6-2 parts of benzoyl peroxide; the modified allyl polyether derivative is obtained by carboxylating the end of the allyl polyether and then connecting an azo dye molecule; the modified silicon dioxide is obtained by surface-modifying nano-silica using a silane coupling agent and then connecting an antioxidant molecule.
[0007] Furthermore, the preparation method of the modified allyl polyether derivative comprises the following steps:
[0008] Ⅰ. Use N,N-dimethylformamide to dissolve allyl polyether and succinic anhydride, control the temperature to 60-75°C, stir for 1-3 hours, wait for the reaction to be completed, remove low-boiling substances by vacuum distillation, filter out the solid sample, and obtain carboxylated allyl polyether;
[0009] Ⅱ. Dissolve the carboxylated allyl polyether in purified water, add Congo red and a catalyst, and stir evenly. Maintain the system temperature at 40-50°C, stir at this constant temperature for 12-24 hours, and perform vacuum distillation. Collect the solid sample, wash the solid 2-3 times with deionized water, and vacuum dry to obtain a modified allyl polyether derivative.
[0010] Through the above technical solution, succinic anhydride has high reaction activity and can undergo a ring-opening esterification reaction with the terminal hydroxyl group of the allyl polyether molecular chain to form an allyl polyether with a terminal carboxyl group, that is, a carboxylated allyl polyether. Under the action of a catalyst, the amino group in the Congo red structure can undergo dehydration condensation with the carboxyl group in the carboxylated allyl polyether structure to obtain a modified allyl polyether derivative with alkenyl groups at both ends and a Congo red structure in the middle.
[0011] Furthermore, in step I, the molecular weight of the allyl polyether is 1000-2000.
[0012] Furthermore, in step II, the catalyst is p-toluenesulfonic acid, and the amount used is 3-5% of the total amount of carboxylated allyl polyether and Congo red.
[0013] Furthermore, the preparation method of the modified silica comprises the following steps:
[0014] ① Ultrasonic dispersion of nano-silica in toluene, addition of 3-aminopropyltriethoxysilane, setting the system temperature to 70-80°C, stirring for 2-8 hours, and after the reaction is complete, centrifugation of the solid sample, washing, and drying to obtain amino-modified silica;
[0015] ②. Add amino-modified silica to tetrahydrofuran, disperse by ultrasonication, add 4-bromo-2,6-di-tert-butylphenol and alkaline catalyst, mix well, increase the system temperature to 60-80°C, react for 4-12 hours, and perform post-treatment on the product to obtain modified silica.
[0016] Through the above technical solution, after the nano-silica is modified with 3-aminopropyltriethoxysilane, the surface is rich in amino groups. Under the action of an alkaline catalyst, it can undergo a nucleophilic substitution reaction with the halogen bromine in the structure of 4-bromo-2,6-di-tert-butylphenol, thereby modifying the antioxidant on the surface of the nano-silica, enhancing the lipophilicity and functionality of the nano-silica, and facilitating the further application of the nano-silica.
[0017] Furthermore, in step ①, the average particle size of the nano-silicon dioxide is 50 nm.
[0018] Furthermore, in step ②, the alkaline catalyst is any one of sodium carbonate or potassium carbonate.
[0019] Furthermore, in step ②, the post-processing process is to separate the solid sample by centrifugation, wash the solid sample with purified water to neutrality, and finally vacuum dry it.
[0020] A method for preparing OCA optical adhesive for folding screens, comprising the following steps:
[0021] A. Mix isobutyl acrylate, butyl acrylate, hydroxyethyl acrylate, glycidyl acrylate and two-thirds of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 60-70°C, and stir for 1-3 hours to obtain OCA optical adhesive pre-emulsion;
[0022] B. Add the modified allyl polyether derivative and the remaining benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 2-4 hours, add the modified silica, stir at a speed of 50-100 rpm for 1-2 hours, and after the stirring is completed, vacuum degassing and let it stand to obtain the OCA optical adhesive latex;
[0023] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After coating, place it in a vacuum drying oven at 50-60°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0024] An application of OCA optical adhesive for folding screens is to apply the OCA optical adhesive for folding screens in the field of preparing folding screens for mobile phones or tablet computers.
[0025] Beneficial effects of the present invention:
[0026] The present invention connects the azo fuel Congo red to the allyl polyether molecular chain to prepare a modified allyl polyether derivative connected by Congo red and containing unsaturated alkenyl functional groups at both ends. The modified allyl polyether derivative is used as a comonomer to participate in the copolymerization process of OCA optical adhesive, so that the prepared OCA optical adhesive structure contains azo groups. The azo groups can absorb blue light at a wavelength of 380-425nm, effectively solving the damage of blue light to the human eye. Moreover, the alkenyl groups at both ends of the modified allyl polyether derivative can serve as cross-linking agents to increase the cross-linking density of the OCA optical adhesive, making the structure of the OCA optical adhesive more compact after curing. Therefore, the OCA optical adhesive has good heat resistance and stability. In addition, the abundant ether bonds in the structure of the modified allyl polyether derivative can generate hydrogen bonds with the adhered substrate, which is beneficial to enhancing the viscosity of the OCA optical adhesive.
[0027] The present invention uses an antioxidant to modify the surface of nano-silica, so that the nano-silica and the OCA optical adhesive matrix have stronger interface properties, can effectively agglomerate the surface nano-silica, and can form physical cross-linking points with nano-silica as the core. Cooperating with the modified allyl polyether derivative cross-linking agent, it can not only make the OCA optical adhesive have stronger tensile strength, but also can utilize the high temperature resistance of nano-silica itself to further enhance the heat resistance stability of OCA optical adhesive, thereby inhibiting the thermal degradation of OCA optical adhesive. At the same time, the antioxidant grafted on the surface of nano-silica can effectively prevent the oxidative decomposition of OCA optical adhesive, making it easier to store and use.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 TG analysis chart of nano-silica, amino-modified silica core-modified silica of the present invention. DETAILED DESCRIPTION
[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0032] Example 1
[0033] 1. Preparation of modified allyl polyether derivatives
[0034] Ⅰ. Dissolve 10 g of allyl polyether and 1.2 g of succinic anhydride in N,N-dimethylformamide, control the temperature to 70°C, stir for 2 hours, wait for the reaction to be completed, remove low-boiling substances by vacuum distillation, filter out the solid sample, and obtain carboxylated allyl polyether, wherein the average molecular weight of the allyl polyether is 1500;
[0035] Ⅱ. Dissolve 5 g of carboxylated allyl polyether in purified water, add 0.6 g of Congo red and 0.2 g of p-toluenesulfonic acid and stir evenly. Maintain the system temperature at 40°C and stir at constant temperature for 16 h. Distill under reduced pressure, collect solid samples, wash the solid three times with deionized water, and dry in vacuo to obtain a modified allyl polyether derivative. The elemental content was analyzed using an EMA 502 elemental analyzer. The test showed that the carbon content, nitrogen content, and sulfur content of the modified allyl polyether derivative were 48.94%, 3.21%, and 2.43%. It is speculated that the carboxyl group in the carboxylated allyl polyether structure and the amino group in the Congo red structure undergo dehydration condensation under the action of p-toluenesulfonic acid to generate a modified allyl polyether derivative with alkenyl groups at both ends and a Congo red structure in the middle. The sulfur and nitrogen elements come from the amino and azo groups in the Congo red structure, and the sulfur element comes from the sulfonic acid group in the Congo red structure.
[0036] 2. Preparation of modified silica
[0037] ①, ultrasonically disperse 5g of nano-silica in toluene, add 2g of 3-aminopropyltriethoxysilane, set the system temperature to 70℃, stir for 6h, wait for the reaction to end, centrifuge and separate the solid sample, wash and dry to obtain amino-modified silica, where the average particle size of nano-silica is 50nm. Take 0.5g of nano-silica and amino-modified silica samples and perform thermogravimetric analysis on the samples using a STA200 thermogravimetric analyzer. The results are as follows: Figure 1 As shown in the figure, it can be seen that nano-silica basically does not decompose, and the weight loss is mainly due to the water adsorbed on the surface. The amino-modified nano-silica decomposes at around 200°C, which is presumably due to the decomposition of 3-aminopropyltriethoxysilane on the surface of the nano-silica. As can be seen from the figure, the grafting rate of 3-aminopropyltriethoxysilane is about 25.3%;
[0038] ②. Add 2g of amino-modified silica to tetrahydrofuran, disperse by ultrasonication, add 0.3g of 4-bromo-2,6-di-tert-butylphenol and 0.5g of sodium carbonate, mix well, raise the system temperature to 70°C, react for 8h, centrifuge to separate the solid sample after the reaction, wash the solid sample with purified water to neutrality, and vacuum dry to obtain modified silica. Similarly, take 0.5g of modified silica sample and perform thermogravimetric analysis on it. The results are as follows: Figure 1 As shown in the figure, it can be seen that the grafting rate of amino-modified silica and 4-bromo-2,6-di-tert-butylphenol is about 17.9%.
[0039] 3. Preparation of OCA optical adhesive
[0040] A. Mix 50 parts of isobutyl acrylate, 20 parts of butyl acrylate, 2 parts of hydroxyethyl acrylate, 1 part of glycidyl acrylate and 0.4 parts of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 60°C, and stir for 1 hour to obtain OCA optical adhesive pre-emulsion;
[0041] B. Add 0.5 parts of modified allyl polyether derivative and 0.2 parts of benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 2 hours, add 1 part of modified silica, stir at a speed of 50 rpm for 1 hour, and after stirring, vacuum degas and let it stand to obtain OCA optical adhesive latex;
[0042] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After the coating is completed, place it in a vacuum drying oven at 50°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0043] Example 2
[0044] Preparation of OCA optical adhesive
[0045] A. Mix 55 parts of isobutyl acrylate, 30 parts of butyl acrylate, 4 parts of hydroxyethyl acrylate, 2 parts of glycidyl acrylate and 0.6 parts of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 65°C, and stir for 2 hours to obtain OCA optical adhesive pre-polymer emulsion;
[0046] B. Add 0.8 parts of modified allyl polyether derivative and 0.3 parts of benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 3 hours, add 1.5 parts of modified silica, stir at 80 rpm for 2 hours, and after stirring, vacuum degas and let stand to obtain OCA optical adhesive latex;
[0047] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After the coating is completed, place it in a vacuum drying oven at 50°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0048] The preparation methods of the modified allyl polyether derivative and modified silicon dioxide are the same as those in Example 1.
[0049] Example 3
[0050] Preparation of OCA optical adhesive
[0051] A. Mix 60 parts of isobutyl acrylate, 40 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate, 3 parts of glycidyl acrylate and 1 part of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 70°C, and stir for 3 hours to obtain OCA optical adhesive pre-polymer emulsion;
[0052] B. Add 1 part of modified allyl polyether derivative and 0.5 part of benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 4 hours, add 2 parts of modified silica, stir at a speed of 100 rpm for 2 hours, and after stirring, vacuum degassing and let it stand to obtain OCA optical adhesive latex;
[0053] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After the coating is completed, place it in a vacuum drying oven at 60°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0054] The preparation methods of the modified allyl polyether derivative and modified silicon dioxide are the same as those in Example 1.
[0055] Comparative Example 1
[0056] Preparation of OCA optical adhesive
[0057] A. Mix 55 parts of isobutyl acrylate, 30 parts of butyl acrylate, 4 parts of hydroxyethyl acrylate, 2 parts of glycidyl acrylate and 0.6 parts of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 65°C, and stir for 2 hours to obtain OCA optical adhesive pre-polymer emulsion;
[0058] B. Add 0.8 parts of modified allyl polyether derivative and 0.3 parts of benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 3 hours, and after the stirring is completed, vacuum degassing and let it stand to obtain OCA optical adhesive latex;
[0059] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After the coating is completed, place it in a vacuum drying oven at 50°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0060] The preparation method of the modified allyl polyether derivative is the same as that in Example 1.
[0061] Comparative Example 2
[0062] A. Mix 55 parts of isobutyl acrylate, 30 parts of butyl acrylate, 4 parts of hydroxyethyl acrylate, 2 parts of glycidyl acrylate and 0.9 parts of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 65°C, and stir for 2 hours to obtain OCA optical adhesive pre-emulsion;
[0063] B. Add 1.5 parts of modified silica to the OCA optical adhesive pre-emulsion, stir at 80 rpm for 2 hours, vacuum degassing after stirring, and let it stand to obtain OCA optical adhesive latex;
[0064] C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After the coating is completed, place it in a vacuum drying oven at 50°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
[0065] The preparation method of the modified silicon dioxide is the same as that in Example 1.
[0066] Performance testing
[0067] (1) With reference to GB / T 2410-2008, the transmittance of the OCA optical adhesives prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was tested. The transmittance of the OCA optical adhesives prepared in Examples 1 to 3 and Comparative Examples 1 and 2 in the 380-450nm blue light band was tested using a UV-1600PC ultraviolet-visible spectrophotometer to evaluate the blue light protection effect. The test results are shown in the following table:
[0068] Table 1 - Optical performance test results
[0069]
[0070] It can be seen from the above table that the OCA optical adhesives prepared in Examples 1 to 3 and Comparative Example 1 all have high light transmittance and low blue light transmittance, which means that they have good anti-blue light effect. Although the OCA optical adhesive prepared in Comparative Example 2 has high light transmittance, its blue light transmittance is also high. It is speculated that this is because the OCA optical adhesive prepared in Comparative Example 2 does not use allyl polyether modified with azo dye Congo red as raw material, and the structure does not contain functional groups that can absorb blue light, so the anti-blue light effect is poor.
[0071] (2) With reference to GB / T 30776-2014, the OCA optical adhesives prepared in Examples 1 to 3 and Comparative Examples 1 and 2 of the present invention were subjected to a tensile performance test. The OCA optical adhesives were placed in a constant temperature drying oven at 100°C for accelerated aging for 200 hours, and then subjected to a tensile performance test. The tensile strength retention rate was calculated, and the tensile strength and aging resistance of the OCA optical adhesives were evaluated. The test results are shown in the following table:
[0072] Table 2 - Tensile properties test results
[0073]
[0074] It can be seen from the above table that the OCA optical adhesives prepared in Examples 1 and 3 of the present invention have excellent tensile properties, and after the accelerated aging test, the tensile strength retention rate shows a high level, so the aging resistance is good. The OCA optical adhesive prepared in Comparative Example 1 has average tensile strength, and after the accelerated aging test, the tensile strength decreases significantly, and the tensile strength retention rate is low, so the aging resistance is poor. The OCA optical adhesive prepared in Comparative Example 2 has average tensile strength, but after the accelerated aging test, the tensile strength retention rate shows excellent performance. It is speculated that the addition of modified silica has a greater impact on the aging resistance of the OCA optical adhesive.
[0075] (3) 0.5 g of the OCA optical adhesive prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 and 2 was cut out and placed in a STA200 thermogravimetric analyzer. Under nitrogen protection, the temperature was increased from 25°C to 500°C at a heating rate of 5°C / min. The initial decomposition temperature of the OCA optical adhesive was recorded, and its heat stability was evaluated. The test results are shown in the following table:
[0076] Table 3 - Heat stability test results
[0077]
[0078] It can be seen from the above table that the OCA optical adhesives prepared in Examples 1 to 3 of the present invention have a higher initial decomposition temperature and good heat resistance stability, while the OCA optical adhesives prepared in Comparative Examples 1 and 2 have a relatively low initial decomposition temperature and relatively general heat resistance stability.
[0079] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0080] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. An OCA optical adhesive for folding screen, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of isodecyl acrylate, 20-40 parts of butyl acrylate, 2-5 parts of hydroxyethyl acrylate, 1-3 parts of glycidyl acrylate, 0.5-1 parts of modified allyl polyether derivative, 1-2 parts of modified silicon dioxide, and 0.6-1.5 parts of benzoyl peroxide; the modified allyl polyether derivative is prepared by carboxylating the end of the allyl polyether and then attaching an azo dye molecule; The modified silica is prepared by surface-modifying nano-silica using a silane coupling agent and then connecting antioxidant molecules; The preparation method of the modified allyl polyether derivative comprises the following steps: Ⅰ. Use N,N-dimethylformamide to dissolve allyl polyether and succinic anhydride, control the temperature to 60-75°C, stir for 1-3 hours, wait for the reaction to be completed, remove low-boiling substances by vacuum distillation, filter out the solid sample, and obtain carboxylated allyl polyether; II. Dissolve the carboxylated allyl polyether in purified water, add Congo red and a catalyst, and stir evenly. Maintain the system temperature at 40-50°C, stir at this constant temperature for 12-24 hours, and perform vacuum distillation. Collect a solid sample, wash the solid 2-3 times with deionized water, and vacuum dry to obtain a modified allyl polyether derivative. The preparation method of the modified silicon dioxide comprises the following steps: ① Ultrasonic dispersion of nano-silica in toluene, addition of 3-aminopropyltriethoxysilane, setting the system temperature to 70-80°C, stirring for 2-8 hours, and after the reaction is complete, centrifugation of the solid sample, washing, and drying to obtain amino-modified silica; ②. Add amino-modified silica to tetrahydrofuran, disperse by ultrasonication, add 4-bromo-2,6-di-tert-butylphenol and alkaline catalyst, mix well, increase the system temperature to 60-80°C, react for 4-12 hours, and perform post-treatment on the product to obtain modified silica.
2. The OCA optical adhesive for folding screen according to claim 1, characterized in that: In step I, the molecular weight of the allyl polyether is 1000-2000.
3. The OCA optical adhesive for folding screen according to claim 1, characterized in that: In step II, the catalyst is p-toluenesulfonic acid, and the amount used is 3-5% of the total amount of carboxylated allyl polyether and Congo red.
4. The OCA optical adhesive for folding screen according to claim 1, characterized in that: In step ①, the average particle size of the nano-silicon dioxide is 50 nm.
5. The OCA optical adhesive for folding screen according to claim 1, characterized in that: In step ②, the alkaline catalyst is any one of sodium carbonate or potassium carbonate.
6. The OCA optical adhesive for folding screen according to claim 1, characterized in that: In step ②, the post-treatment process is to separate the solid sample by centrifugation, wash the solid sample with purified water until it is neutral, and finally vacuum dry it.
7. A method for preparing an OCA optical adhesive for a folding screen according to claim 1, characterized in that: The preparation method comprises the following steps: A. Mix isodecyl acrylate, butyl acrylate, hydroxyethyl acrylate, glycidyl acrylate and two-thirds of benzoyl peroxide, pour into a reactor, pass nitrogen for protection, increase the temperature in the reactor to 60-70°C, and stir for 1-3 hours to obtain OCA optical adhesive pre-emulsion; B. Add the modified allyl polyether derivative and the remaining benzoyl peroxide to the OCA optical adhesive pre-emulsion, continue stirring for 2-4 hours, add the modified silica, stir at a speed of 50-100 rpm for 1-2 hours, and after the stirring is completed, vacuum degassing and let it stand to obtain the OCA optical adhesive latex; C. Use the scraping method to evenly apply the OCA optical adhesive latex on the heavy release film. After coating, place it in a vacuum drying oven at 50-60°C for curing. When it reaches a solidified state, cover its surface with a light release film to obtain the OCA optical adhesive for folding screens.
8. An application of the OCA optical adhesive for folding screens according to claim 1, characterized in that: The OCA optical adhesive for folding screens is used in the field of preparing folding screens for mobile phones or tablet computers.
Citation Information
Patent Citations
High-performance OCA (Optical Clear Adhesive) for folding screen and preparation method of high-performance OCA
CN114907781A
Reinforcing and anti-aging environment-friendly rubber aging inhibitor and preparation method and application thereof
CN106349505A
OCA (Optical Clear Adhesive), adhesive film and preparation method thereof
CN113717666A